Hybrid Resilience: The Transformation of Indonesian Islamic Education in Response to Digital Polarization and Global Challenges - St Robiatul Adawiyah; Tri Wahyudi Ramdhan; Yuldashev Azim Abdurakhmonovich (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2026)
In the midst of the escalation of ideological polarization and social segregation due to digital disruption, Islamic educational institutions in Indonesia face a double demand: maintaining religious orthodoxy while responding to the challenges of society 5.0. This research aims to map the transformation of the Islamic education curriculum and pedagogy, moving from the teaching of passive tolerance to the formation of active social resilience. Using the Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol, this study analyzed 48 selected empirical articles (2015–2025) focusing on the dynamics of Islamic education in post-conflict and multicultural areas. The findings show the emergence of the